2015
DOI: 10.1177/1087054715620897
|View full text |Cite
|
Sign up to set email alerts
|

Receiver Operating Characteristic Curve Analysis of Screening Tools for Bipolar Disorder Comorbid With ADHD in Schoolchildren

Abstract: The CBCL-PBD and P-YMRS can be used to screen for manic behavior and assist in differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
3
4
0
Order By: Relevance
“…ROC analysis using data from four independent large data sets of children with and without a structured interview derived diagnosis of BP-I disorder showed that a combined t-score of 195 on the CBCL-BP profile efficiently identified children with pediatric BP-I disorder. These results support and extend previous results (9)(10)(11)(12)(13) and provide strong evidence that the CBCL-BP profile is a useful tool to help identify youth who may have BP-I disorder.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…ROC analysis using data from four independent large data sets of children with and without a structured interview derived diagnosis of BP-I disorder showed that a combined t-score of 195 on the CBCL-BP profile efficiently identified children with pediatric BP-I disorder. These results support and extend previous results (9)(10)(11)(12)(13) and provide strong evidence that the CBCL-BP profile is a useful tool to help identify youth who may have BP-I disorder.…”
Section: Discussionsupporting
confidence: 89%
“…The CBCL is an empirically derived broadband assessment tool of psychopathology with excellent psychometric properties that has been translated into over 100 languages and is an easy to use paper and pencil instrument. A body of research (9)(10)(11)(12) and a meta-analysis (13) have shown very high correspondence between a unique profile of the CBCL consisting of elevations in the Attention, Anxiety/Depression and Aggression subscales greater than two standard deviations (SDs) above the norm (≥ 210 combined) with structured diagnostic interview derived clinical diagnosis of pediatric BP disorder (hence termed the CBCL-BP profile). However, because some studies failed to find an association between the CBCL-BP profile and a diagnosis of pediatric BP disorder, (14)(15)(16)(17)(18), there is a clear need for further evaluation of the utility of the CBCL to help identify children who may have BP disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Although our results demonstrating the very high efficiency of the CBCL-BP profile in identifying children with pediatric BP-I disorder are consistent with previous research in a sample of youth with and without ADHD and their siblings (10), in a sample of Brazilian children (12), and in a meta-analysis (13), data from two community samples of treatmentseeking youth did not find an association between the CBCL-BP profile with pediatric BP spectrum disorder (18,31). Although the reasons for these discrepancies are not entirely clear, several explanations are plausible.…”
Section: Discussionsupporting
confidence: 92%
“…The CBCL is an empirically derived broadband assessment tool of psychopathology with excellent psychometric properties that has been translated into over 100 languages and is an easy to use paper and pencil instrument. A body of research (9)(10)(11)(12) and a meta-analysis (13) have shown very high correspondence between a unique profile of the CBCL consisting of elevations in the Attention, Anxiety/Depression and Aggression subscales greater than two standard deviations (SDs) above the norm (≥ 210 combined) with structured diagnostic interview derived clinical diagnosis of pediatric BP disorder (hence termed the CBCL-BP profile). However, because some studies failed to find an association between the CBCL-BP profile and a diagnosis of pediatric BP disorder, (14)(15)(16)(17)(18), there is a clear need for further evaluation of the utility of the CBCL to help identify children who may have BP disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The scales constituting the ASEBA, developed by Achenbach and Rescorla (2001), have been used in several countries to track a wide range of mental health problems in childhood and adolescence (Dekker et al 2002;Cordeiro et al 2016;Raiker et al 2017). Assessment Data Manager is the ASEBA software that enables the analysis and comparison of data from multiple informants.…”
Section: Child Behaviour Checklist and Teacher's Report Formmentioning
confidence: 99%